(untitled) (Praxis Educativa, 2023)
This article is part of my research work entitled "The marks of evaluation: an interpretive study of the (auto) biographies of teachers of initial level of the Kindergarten 922 of Mar del Plata" which tries to think the pedagogical practice from (auto) biographical stories. In this research, the voices of teachers, interviewed during the fieldwork, are intertwined with my own professional experiences, creating a text in which the concepts of autobiography, identity and evaluation are combined and intertwined. This recreates multiple stories that make visible the task of teaching and learning. Moreover, they allow delving into vital experiences that make up the subjectivity and structuring of the teaching identity.